If it's not what You are looking for type in the equation solver your own equation and let us solve it.
26(x-2)+3(4-x)=25
We simplify the equation to the form, which is simple to understand
26(x-2)+3(4-x)=25
Reorder the terms in parentheses
+(+26x-52)+3*(4-x)=25
Remove unnecessary parentheses
+26x-52+3+*(+4-x+)=+25
Reorder the terms in parentheses
+26x-52+(+12-3x)=25
Remove unnecessary parentheses
+26x-52+12-3x=+25
We move all terms containing x to the left and all other terms to the right.
+26x-3x=+25+52-12
We simplify left and right side of the equation.
+23x=+65
We divide both sides of the equation by 23 to get x.
x=2.8260869565217
| 0.75x+13.25=1.25x+12 | | 7x+2x+4x-10x-x=20 | | (2.4x)+11.3=3.7-(0.6x) | | 70-2x=210-42x | | -2x-2(3x+5)=-106 | | 2x^2+25x-3=0 | | X-4(2X-3)=26 | | 2x^2=82 | | 2=2.27-s-4 | | .09n=600-0.12n+198 | | X-4(2X-30)=26 | | -2x-4(-6-10)=-136 | | 5u+11=111 | | 6n+24= | | 67-2x=83-3x | | 0.22m=0.1m+15.60 | | (5x^3y/20xy^5)^4 | | 13X=-X^2-12 | | (12x+7)+(3x^2-12x-5)= | | 3x^2-32x+75=0 | | 26x-2=8x+3+85 | | 502.08+1.6= | | -20=1/3n--10 | | -4+2v=4(v-4) | | 2x+6+3x=7+2x+8 | | 5z+8z=Z-2-9z | | 10=5+v | | 8x+9=6x+32 | | -5/4x-2=-8 | | 2(6)+4y=24 | | y=1/2cos2x | | -20=1/3n-10 |